HEALTH INFORMATION SYSTEMS AND INTELLIGENT INFORMATION SYSTEMS – FUNDAMENTALS - Oliveira, Lismary Barbosa de; Braga, Renata Dutra; Provin, Mércia Pandolfo (CIPEEX, 2025)
This paper explores the fundamental concepts of Health Information Systems (HIS) and Intelligent Information Systems (IIS), highlighting their functions in capturing, storing, and processing digital health information. The methodology employed was a literature review, focusing on understanding how these systems contribute to information management and decision-making in the health sector. The results revealed that HIS play a crucial role in the organization and accessibility of data, while IIS, by incorporating artificial intelligence, enable the generation of new data and insights, optimizing processes and supporting strategic decisions. It is concluded that the integration and evolution of these systems are essential for the efficiency and effectiveness of health services, providing more informed and targeted management.